2012
DOI: 10.1002/pssa.201127712
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial La0.7Sr0.3MnO3 thin films grown on SrTiO3 buffered silicon substrates by reactive molecular‐beam epitaxy

Abstract: La 0.7 Sr 0.3 MnO 3 (LSMO) thin films (with a thickness of 10, 20, 60, 75, and 100 nm) were grown on SrTiO 3 (STO)-buffered silicon (001) substrates by reactive molecular-beam epitaxy. Xray diffraction (XRD) revealed the heterostructures to be fully epitaxial with orientation relationship (001) LSMO jj (001) STO jj (001) Si and [100] LSMO jj [100] STO jj [110] Si. Root mean square roughness was about 0.5 nm as measured by atomic force microscopy (AFM) for films of 10-75 nm thicknesses, and about 1 nm for the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 34 publications
3
25
0
Order By: Relevance
“…Insulating behavior over the whole temperature range is observed. This leads us to conclude that both the electrical and magnetic properties are enhanced compared to those reported in high epitaxial quality La 0.7 Sr 0.3 MnO 3 films deposited on SrTiO 3 buffered Si substrates, 39 where T MI and T C values were 350 K and 330 K, respectively. We ascribe the enhancement of these properties to the fact that the La 0.7 Sr 0.3 MnO 3 cell is under compressive in-plane strain on CaTiO 3 /Si as predicted by Millis et al 57 and also experimentally observed in Ref.…”
Section: -mentioning
confidence: 65%
See 4 more Smart Citations
“…Insulating behavior over the whole temperature range is observed. This leads us to conclude that both the electrical and magnetic properties are enhanced compared to those reported in high epitaxial quality La 0.7 Sr 0.3 MnO 3 films deposited on SrTiO 3 buffered Si substrates, 39 where T MI and T C values were 350 K and 330 K, respectively. We ascribe the enhancement of these properties to the fact that the La 0.7 Sr 0.3 MnO 3 cell is under compressive in-plane strain on CaTiO 3 /Si as predicted by Millis et al 57 and also experimentally observed in Ref.…”
Section: -mentioning
confidence: 65%
“…The normalized Hooge parameters α H /n was then measured to be (4.2 ± 0.6) × 10 −31 m 3 at 300 K, which is about two times lower than the one measured in La 0.7 Sr 0.3 MnO 3 films of comparable thickness deposited on SrTiO 3 /Si with α H /n values of (9.8 ± 0.6) × 10 −31 m 3 at 300 K and only two times higher than the one measured in La 0.7 Sr 0.3 MnO 3 films of comparable thickness deposited on SrTiO 3 single crystal substrates with α H /n values of (2.47 ± 0.6) × 10 −31 m 3 . 39,58,59 In conclusion, we have shown the promise of epitaxial (100) p -oriented CaTiO 3 as a buffer layer for the integration of functional oxides having the perovskite structure with silicon. Specifically, we have grown high-quality epitaxial La 0.7 Sr 0.3 MnO 3 films on CaTiO 3 /Si.…”
Section: -mentioning
confidence: 77%
See 3 more Smart Citations